Characterisation of oxidation and wear oxidised surfaces of H13 steel/brass in dry sliding conditions. (8th October 2013) - Kchaou, Mohamed; Alimi, Amel; Elleuch, Riadh; Desplanques, Yannick
Although oxide scale has significant influence on surface quality of hot–worked products, deformation of the scale during hot working has not been understood sufficiently. The authors propose an experimental study to analyse the oxidation and the tribological behaviour of a ferrous alloy (X40CrMoV5–1, H13 steel) and non ferrous alloy (CuZn39Pb3, brass alloys) in dry sliding conditions. The tribological behaviour of the pair of materials is carried out on a pin–on disk wear tester after oxidation at 600°C for 70 h. It was found that: i) a loose oxide film wholly covered the surface of the steel; ii) Fe2 O3 as the main oxide was identified except for a small amount of Fe3 O4 ; iii) during friction, a compacted oxide film was established on the worn surface of the steel. The analysis of the worn surface showed two regions: a delamination region due to the delamination of tribo–oxide during wear and an undelamination region characterised by the dominance of Fe3 O4 tribo–oxides on the worn surface.